The Utilization of Isolation Chromophore in an "A3+B2" Type Second‐Order Nonlinear Optical Hyperbranched Polymer. Issue 13 (27th May 2013) - Wu, Wenbo; Ye, Cheng; Qin, Jingui; Li, Zhen
Abstract In this paper, a new nonlinear optical (NLO) hyperbranched polymer P1 is designed and synthesized successfully through one‐pot "A3+B2" approach via a simple Sonogashira coupling reaction, in which isolation chromophore is introduced to improve its comprehensive performance such as NLO activity, optical transparency, and stability. For comparison, its analogs, P2 and P3, just containing one type of chromophore, are also prepared. Although P1 cannot be well poled under our test conditions, its NLO coefficient is still much higher than its analogs P2, P3, and the linear polyaryleneethynylene P4, which also contains isolation chromophore, indicating the advantages of isolation chromophore and the three‐dimensional (3D) spatial isolation from the highly branched structure in the NLO field.<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>